Yesus Satu-Satunya Pemberi Kemerdekaan Bagi Orang Berdosa - Fenius Gulo (Jurnal Teologi dan Pelayanan Kerusso, 2021)
This study is aimed to analyze John 8:36 regarding the meaning of the phrase "So if the Son sets you free, you will be free indeed," with a qualitative research method and biblical study approach. The main source of this research is the Bible and some other literatures as support sources and used as a comparison material. After conducting a very careful investigation, it is confirmed that the only person who is worthy of giving freedom to sinners is Jesus Christ the Son of God. Belief in Jesus is the key to freedom and the freedom from the bondage of sin. Abstrak indonesia Penelitian ini bertujuan untuk menganalisis Yohanes 8:36 mengenai makna frasa “apa bila Anak itu memerdekakan kamu, kamupun benar-benar merdeka,” dengan metode penelitian kualitatif dengan pendekatan study biblika. Sumber utama pada penelitian ini adalah Alkitab dan literarur lainnya sebagai pendukung dan dijadikan sebagai bahan perbandingan. Setelah melakukan penyelidikan yang sangat hati-hati, menyungguhkan bahwa satu-satunya pribadi yang layak member kemerdekakaan bagi orang berdosa adalah hanya sang Anak yaitu Yesus Kristus. Kepercayaan kepada Yesus merupakan kunci kemerdekaan dan terbebaskan dari belenggu dosa.